2017
DOI: 10.7586/jkbns.2019.21.1.22
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Health-related Quality of Life in Patients with Advanced Heart Failure

Abstract: Purpose: Even though advanced heart failure (HF) severely affects the patient' s health-related quality of life (HRQoL), there is little information regarding this issue. This review is aimed to describe the relevant clinical characteristics of patient with advanced HF and identify factors influencing HRQoL in these patients. Methods: Empirical articles were searched from electronic databases issued from January 2000 to June 2018 with using the key terms 'heart failure' and 'quality of life'. There were a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Next, symptoms were found to be a significant indirect influencing factor on QoL through functional limitations. This is supported by the results of an integrated review that reported that the greater the physical symptom severity, the poorer the QoL 15 . Experiencing exacerbated HF symptoms impact patients' QoL and create significant disruptions in their lives 6 .…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Next, symptoms were found to be a significant indirect influencing factor on QoL through functional limitations. This is supported by the results of an integrated review that reported that the greater the physical symptom severity, the poorer the QoL 15 . Experiencing exacerbated HF symptoms impact patients' QoL and create significant disruptions in their lives 6 .…”
Section: Discussionmentioning
confidence: 88%
“…This is supported by the results of an integrated review that reported that the greater the physical symptom severity, the poorer the QoL. 15 Experiencing exacerbated HF symptoms impact patients' QoL and create significant disruptions in their lives. 6 Proper treatment can be delayed because major symptoms are not identified early, yet many patients had potential HF symptoms in the months before acute care visits.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations